2011
DOI: 10.1007/s12307-011-0075-6
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β in the Bone Microenvironment: Role in Breast Cancer Metastases

Abstract: Breast cancer is the most prevalent cancer among females worldwide. It has long been known that cancers preferentially metastasize to particular organs, and bone metastases occur in ∼70% of patients with advanced breast cancer. Breast cancer bone metastases are predominantly osteolytic and accompanied by bone destruction, bone fractures, pain, and hypercalcemia, causing severe morbidity and hospitalization. In the bone matrix, transforming growth factor-β (TGF-β) is one of the most abundant growth factors, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 195 publications
(204 reference statements)
1
50
0
Order By: Relevance
“…The overexpression of certain tumorigenesis-related factors such as VEGF-C, ICAM-1 and TGF-β has been observed in numerous tumors, indicating that these factors may play important roles in tumor initiation, growth, and development (Roskoski, 2007;Buijs et al, 2011;Kotteas et al, 2014). VEGF-C regulates angiogenesis, an indispensable mechanism in living organisms that controls proliferation, development, and reproduction in normal tissue as well as cancer tissue.…”
Section: Journal Of Agricultural Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…The overexpression of certain tumorigenesis-related factors such as VEGF-C, ICAM-1 and TGF-β has been observed in numerous tumors, indicating that these factors may play important roles in tumor initiation, growth, and development (Roskoski, 2007;Buijs et al, 2011;Kotteas et al, 2014). VEGF-C regulates angiogenesis, an indispensable mechanism in living organisms that controls proliferation, development, and reproduction in normal tissue as well as cancer tissue.…”
Section: Journal Of Agricultural Sciencementioning
confidence: 99%
“…Moreover, various tumorigenesis-related factors such as transforming growth factor beta (TGF-β), vascular endothelial growth factor-C (VEGF-C), and intracellular cell adhesion molecule-1 (ICAM-1) have been shown to participate in tumor growth and dissemination (Roskoski, 2007;Buijs et al, 2011;Kotteas et al, 2014). de Jong et al, have demonstrated that TGF-β expression levels correlated with angiogenesis and prognosis of breast cancer patients (de Jong et al, 1998).…”
mentioning
confidence: 99%
“…It is a potent inducer of epithelial-mesenchymal transition of cancer cells, an event thought to be critical for tumor dissemination, and also mediates communication of cancer cells with other tumor components during metastasis of cancer cells to various organs (4)(5)(6)50). TGF-β is of particular importance in bone metastasis because of its abundance in bone matrix and its pivotal role in the osteolytic vicious cycle (3,51). The pathway has been reported to regulate other prominent pathways, such as PI3K, MAPK, Rho/RAC1, NF-κB, Notch, and TNF-α (52).…”
Section: Dlc1 Expression Is Negatively Associated With Pthlh and Bonementioning
confidence: 99%
“…TGF-β signaling is a critical regulator of breast cancer metastasis to the bone, which is a rich reservoir of various growth factors, such as TGF-β, IGF, and EGF (2,3). TGF-β binds to and activates a pair of cell surface receptors, which in turn phosphorylate SMAD2 and SMAD3.…”
Section: Introductionmentioning
confidence: 99%
“…For example, tumor cell and bone cell secretion of TGF-b has been associated with immunosuppression in the tumor microenvironment. Apart from its well-known role in promoting bone resorption during the 'viscous cycle', 50 TGF-b suppresses the immune response by repressing the production of effector molecules such as perforin, granzymes, Fas-ligand and IFN-g by cytotoxic immune cells 51 and by downregulating the expression of the NKG2D receptor on NK cells in numerous human cancers. 52 Additionally, TGF-b targets the maturation of DCs and the antitumor functionality of macrophages and neutrophils.…”
Section: Indirect Effects On the Immune Milieumentioning
confidence: 99%